EFFECT OF BID CHALLENGE STRUCTURE ON SUPPLY CHAIN MANAGEMENT SCHEME IN KENYA. - Ochola, Philip Onyango; NZULWA, DR. JOYCE (International Journal of Supply Chain and Logistics, 2019)
Purpose: To establish the influence of bid challenge structure on supply chain management in Kenya. Methodology: The study embraced descriptive research design in order to provide a framework to examine current conditions, trends and status of events. The respondents of the study were all published bid challenges cases decisions in PPARB website for a period of three years. The period covered 2011- 2013. The number of bid challenge decided cases was 173 for the study period. Primary data was collected using semi structured questionnaires. These questionnaires were constructed with both open and closed ended questions to enable for quantitative and qualitative analysis respectively. Data was analysed using both descriptive and inferential statistics. Quantitative data was computed descriptively using frequencies and percentages while for inferential statistics regression analysis was conducted at a 5% (0.05) test significance level. Results: Procurement Review coefficient of 0.865 was found to be positive at significant level of 0.0012 and this indicates that Procurement Review has a positive influence on Supply chain projects, (X2) Administrative Review coefficient of 0.868 was found to be positive at significant level of 0.0022 and this indicates that Administrative Review has a positive influence on Supply chain projects, (X3) Judicial Review coefficient of 0.810 was found to be positive at significant level of 0.0019 and this indicates that Judicial Review has a positive influence on Supply chain projects. (X4) Independence of Review Authority coefficient of 0.741 was found to be positive at significant level of 0.001 and this indicates that Independence of Review Authority has a positive influence on Supply chain projects. Unique contribution to policy and practice: The study prescribes that resources need to be more utilized to enable more development and less wastage in the company. The study also recommends the company stakeholders to be actively involved in Supply chain projects.